Songs of the humpback whale : a novel - Picoult, Jodi. (New York : Atria Books, 2007)
If you were harmed as a child and you were afraid your daughter was being harmed - what would you do? Jodi Picoult's first novel is a compelling drama of family, loss and misunderstanding, and reconciliation.
Keywords: Families -- Fiction. -- United States; Marriage -- Fiction. -- United States